Epidemiological and molecular surveillance of norovirus in the Brazilian Amazon: description of recombinant genotypes and improvement of evolutionary analysis - Costa, Jonaia Novaes da; Siqueira, Jones Anderson Monteiro; Teixeira, Dielle Monteiro; Lobo, Patrícia dos Santos; Guerra, Sylvia de Fátima dos Santos; Souza, Isadora Monteiro; Cardoso, Bruna Trindade Moreira; Farias, Luana Silva Soares; Resque, Hugo Reis; Gabbay, Yvone Benchimol; Silva, Luciana Damascena da (Revista do Instituto de Medicina Tropical de São Paulo, 2024)
Noroviruses are highly infectious, genetically diverse viruses. Global outbreaks occur frequently, making molecular surveillance important for infection monitoring. This cross-sectional descriptive study aimed to monitor cases of norovirus gastroenteritis in the Brazilian Amazon. Fecal samples were tested by immunoenzymatic assay, RT-PCR and genetic sequencing for the ORF1/ORF2 and protease regions. Bayesian inference with a molecular clock was employed to construct the phylogeny. The norovirus prevalence was 25.8%, with a higher positivity rate among children aged 0-24 months. Genogroup GII accounted for 98.1% of the sequenced samples, while GI accounted for 1.9% of them. The GII.P16/GII.4 genotype was the most prevalent, with an evolution rate of 2.87x10−3 and TMRCA estimated in 2012. This study demonstrates that norovirus is a primary causative agent of gastroenteritis and provides data on viral genetic diversity that may facilitate infection surveillance and vaccine development.